ANALISIS ENERGI DALAM PROSES PENGOLAHAN KOPRA RAKYAT - Gerson Wohon; Dedie Tooy; Robert Molenaar (Universitas Sam Ratulangi, 2018)
Abstract Â This study aims to determine the energy sources at the stage of the copra processing commonly made by the people, to measure the amount of energy used at each stage of the people's copra processing process, to calculate the total energy used eachs of was obtained by means of energy analysis surveys. The resulting data consists of primary and secondary data. Â The total input energy in the process of people's copra is more than twice the amount of output energy contained in the copra produced (870,840 kcal). This condition indicates the need to improve the efficiency of the copra processing process in energy utilization.. Keywords: Energy of coconut fiber, human energy, livestock energy.